Drowning the body in pain: torture in The Railway Man and Zero Dark Thirty - Rosa, Ketlyn Mara; Rosa, Janaina Mirian (Em Tese, 2019)
The aim of this article is to discuss the characteristics and implications of the depiction of torture in war films, more specifically, in the cinematic analysis of the interrogation and torture sequences in The Railway Man, which is set during the Second World War, and Zero Dark Thirty, a movie that represents the post-9/11 warfare climate. The filmic analysis of the scenes provides an understanding of the portrayal and ramifications of corporeal and emotional pain while also raising a debate on the depiction of the roles of torturer and tortured. Such representations demonstrate the impact of traumatic warfare events in the national imaginary, delving deep into the role of the body and memory as the past resurfaces in the corporealized manifestation of painful sensations.